INTERAKSI STAKEHOLDER DALAM PENGEMBANGAN UMKM MEBEL KAYU DI KABUPATEN WONOGIRI (Studi Kasus UMKM Mebel Kayu di Kecamatan Wonogiri, Kabupaten Wonogiri) - , ASTUTI SETYANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research focusing on interaction between stakeholder are the local Government and employers of Small Medium Enterprises (SMEs). Interaction can occur between individuals with a communication. In this research, interaction influenced by three factors, are Communication, openness and mutual understanding. This research using a qualitative approach. The data obtained through by interviews, literature research and by documentation. Interviews done with key informan and literature research by article, journal and documents. And the conclusion is interaction between stakeholder already established since 1998 ago. The communication factor in interaction between government and private to develop SMEs are informative. The fact are many programs already exist on reclame or invitation for following programs from government, such as workshop and exhibition. At the same time, openness factor in interaction between government hasnât fully openness to public. This can be explained by the fact that the capital development efforts havenât received evenly. And for mutual understanding factors, interaction between stakeholder has been guided by the understanding to improve business. This supported with the holding many programs such as training and coaching are also involve community organizations.